Evangelii Gaudium: A Call to Renewal in the Holy Spirit. (6th December 2018) - Alva, Reginald
Abstract: Renewal and reformation are indispensable for the growth of person or an institution. Every Christian as an individual and as a member of the church community is in need of renewal to proclaim boldly the gospel of Christ and bear witness through their lives. Secularization and depravity of moral values poses serious challenges to the faith life of a Christian. Moreover, the rise in fundamentalism, jingoism, consumerism, social and political inequity, and environmental degradation are breeding a state of hopelessness, angst, and ennui in the society. Christians and the church need spiritual renewal and transformation to be the salt of the earth and the light to the nations. The Holy Spirit is the principal agent of all genuine spiritual renewal and evangelization. Pope Francis, in his Apostolic Exhortation Evangelii Gaudium, invites all Christians and the church itself to seek renewal in the Holy Spirit by having a personal encounter with Jesus Christ and grow in his discipleship. In this paper, I shall examine the concrete steps the church and Christians need to take for genuine renewal in the Holy Spirit to do the work of evangelization, in the light of the teachings of Evangelii Gaudium . The main source for this paper is Evangelii Gaudium and other church documents.